Effects of arsenic toxicity on morphological characters in blackgram (Vigna mungo L.) during early growth stage - Shamim, M. Z.; Pandey, A. (Cellular and Molecular Biology, 2017)
Blackgram is an important pulse crop of the tropic and sub-tropic area and has been identified as a potential crop in many countries. In the south-East Asia arsenic toxicity in soil and water is one of the most environmental problems. Crop productivity is highly affected by cultivation in arsenic polluted soil or irrigation through arsenic polluted water. The present study was conducted to evaluate the effect of arsenic (As) on fresh shoot length, fresh shoot weight, fresh root length, fresh shoot weight and total fresh biomass, The results indicate that root length is more affected than shoot length due to arsenic toxicity. The fresh shoot weight observed was more affected than fresh root weight. This study indicates that arsenic toxicity causes the deleterious effect on blackgram growth. The toxic effect of blackgram depends on the genotypic variability. Some blackgram genotypes show very less toxic effect of arsenic due to its genetic makeup. Experimental findings of study indicate that longer root length and more shoot weight in arsenic stress condition may be tolerant blackgram genotype to arsenic toxicity.